The Changes of Irisin and Inflammatory Cytokines in the Age-Related Macular Degeneration and Retinal Vein Occlusion - Li, Xiaochun; Cao, Xiaoguang; Zhao, Mingwei; Bao, Yongzhen (Frontiers in Endocrinology, 2022)
Purposes: Age-related macular degeneration (AMD) and retinal vein occlusion (RVO) are irreversible chorioretinal diseases, which might induce severe damage of visual function. The metabolic factor and inflammatory factors might play important roles in the pathogenesis of AMD and RVO. The levels of irisin and 14 cytokines were analyzed in aqueous humor of AMD and RVO eyes, and to evaluate the roles of irisin and inflammatory factors. Methods: We collected aqueous humor samples from patients with AMD (n=27), RVO (n=30) and cataract (as control, n=23) eyes. Samples were assayed using ELISA kit for irisin and a multiplex immunoassay kit for 14 cytokines. The macular thickness (MT) was measured with OCT in all included eyes. Results: MT in RVO higher than that in AMD or the control significantly. Irisin levels in the aqueous samples of AMD and RVO eyes were both significantly lower than in the control. Furthermore, a positive correlation was found between irisin and MT in the RVO. Compared with the controls, AMD eyes had significant higher levels of BDNF, VEGF-A, VEGF-R1, VEGF-R2, IL-10, TNF-α, VCAM-1, IP-10 and MCP-1. Similarly, RVO eyes had significant higher levels of BDNF, VEGF-A, VEGF-R1, VEGF-R2, IL-6, IL-8, IL-10, TNF-α, ICAM-1, VCAM-1, IP-10 and MCP-1. However, there was no significant difference between the levels of PDGF-BB or TNF-β in these three groups. A negative correlation was found between VEGF-A and MT in AMD, and also in control. Furthermore, a positive correlation was found between IL-6 and MT in the total 80 included eyes, and also in RVO. And a positive correlation was found between ICAM-1 and MT in the total 80 included eyes, and also in RVO. Conclusions: The metabolic factor, irisin levels in the aqueous humor are decreased in AMD and RVO eyes and show a positive correlation between irisin and macular thickness in RVO eyes, which indicates a new direction to explore the relationship between irisin and macular edema. We also identified the higher expression of vascular growth factors, VEGF-A, VEGF-R1 and PDGF-BB, inflammatory cytokines, IL-6, IL-8, IL-10 and TNF-α, the chemokines, ICAM-1, VCAM-1, IP-10 and MCP-1, in AMD and RVO eyes.